EFEKTIVITAS JAHE TERHADAP PENURUNAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - ida safitri (Poltekkes Kemenkes Medan, 2021)
Introduction: nausea and vomiting are often experienced by pregnant women, especially at a young gestational age. The occurrence of nausea and vomiting at a young gestational age is due to hormonal changes that occur in every pregnant woman. According to data from the World Health Organization, 12.5% ??of pregnant women experience Hyperemesis Gravidarum and usually attacks at a young age. There are several therapies that can be used to reduce nausea and vomiting in pregnant women, one of which is therapy with ginger drinks. Methods: International and domestic literature were traced through several media using keywords as the PICO formula. The articles selected were 8, 5 foreign and 3 domestic, each of which had its own results. Results: There are differences in results that indicate the level of effectiveness of ginger in the incidence of hyperemesis gravidarum in pregnant women. Discussion: there are many pharmacological ways that can be given for the occurrence of hyperemesis gravidarum, but there are also non-pharmacological or herbal methods that we can provide for the occurrence of hyperemesis gravidarum, one of which is ginger therapy. For ginger, it can be processed in various kinds, some are in powder form and some are in the form of rhizome. Conclusion: After analyzing ginger, it can be concluded that ginger is effective in reducing hyperemesis gravidarum. Key words: Hyperemesis Gravidarum; pregnant women; Ginger